Quality Kualitas pelayanan kepada nasabah di koperasi BMT ‎Sarana Wiraswasta Muslim - Rahmawati, Laila (Maliki Interdisciplinary Journal, 2023)
The service that will be received by customers is in accordance with expectations, the quality of service is quite good, otherwise if the service received is less than expected, it can be perceived as bad. Therefore, employee service depends on the ability possessed so that it can meet customer expectations consistently. The purpose of this study is to assess the quality of service to customers at the BMT Sarana Wiraswasta Muslim Cooperative. This research uses descriptive with qualitative approach method. This research was conducted during the implementation of PKL (Field Work Practice) activities from June to July. The data obtained is in the form of primary data from direct observations during PKL (Field Work Practice). Research results of service quality there are several factors namely physical evidence, assurance, empathy, reliability and responsiveness.